Effect finishing and polishing procedures on the surface roughness of IPS Empress 2 ceramic - Boaventura, Juliana Maria Capelozza [UNESP]; Nishida, Rodrigo [UNESP]; Elossais, André Afif; Lima, Darlon Martins; Reis, José Mauricio Santos Nunes [UNESP]; Campos, Edson Alves [UNESP]; Andrade, Marcelo Ferrarezi de [UNESP] (MJS Publishing, Medical Journals Sweden AB, 2013)
Objective. To evaluate the surface roughness of IPS Empress 2 ceramic when treated with different finishing/polishing protocols. Materials and methods. Sixteen specimens of IPS Empress 2 ceramic were made from wax patterns obtained using a stainless steel split mold. The specimens were glazed (Stage 0-S0, control) and divided into two groups. The specimens in Group 1 (G1) were finished/polished with a KG Sorensen diamond point (S1), followed by KG Sorensen siliconized points (S2) and final polishing with diamond polish paste (S3). In Group 2 (G2), the specimens were finished/polished using a Shofu diamond point (S1), as well as Shofu siliconized points (S2) and final polishing was performed using Porcelize paste (S3). After glazing (S0) and following each polishing procedure (S1, S2 or S3), the surface roughness was measured using TALYSURF Series 2. The average surface roughness results were analyzed using ANOVA followed by Tukey post-hoc tests (α = 0.01) Results. All of the polishing procedures yielded higher surface roughness values when compared to the control group (S0). S3 yielded lower surface roughness values when compared to S1 and S2. Conclusions. The proposed treatments negatively affected the surface roughness of the glazed IPS Empress 2 ceramic. © 2013 Informa Healthcare.
Keywords: Ceramics; Dental polishing; Surface roughness